Tunable production of succinic acid at elevated pressures of CO2 in a high pressure gas fermentation reactor. (August 2020) - Amulya, K.; Kopperi, Harishankar; Venkata Mohan, S.
Highlights: Elevated pressures of CO2 contributed for enhanced production of succinic acid (SA). Highest SA titers, yields and productivities were achieved at 2 bar pressures. Elevated pressures promoted shifts in by-product formation. Converting CO2 to SA provides scope for abatement of CO2 emissions. Abstract: Production of bio-based alternative of succinic acid (SA) has been growing due to the awareness on environmental advantages it offers, such as CO2 sequestration. Current study focuses on evaluating the impact of different CO2 partial pressures (0.6, 0.8, 1, 2 bar) on SA production and yield as well as on other parameters like acids profile and CO2 fixation rate in Citrobacter amalonaticus . Increasing partial pressure to 2 bar enhanced SA production and maximum of 14.86 gL −1 was achieved with a productivity of 0.36 gL −1 h −1 and yield of 52.10%. Varying partial pressures depicted significant influence on total acids profile, where at lower pressures (0.6 bar) lactic (5.6 gL −1 ) and acetic acids (4.1 gL −1 ) became dominant products, while concentration of SA was 2.07 gL −1, by the end of cycle. The desirable effect of moderately elevated pressures for converting CO2 to platform chemicals can be a potential strategy in overcoming current challenges related to CO2 abatement.